Measuring Trainee Translators’ Knowledge of German Culture. Design and Validation of a Cultural Declarative Knowledge Questionnaire - Olalla-Soler, Christian (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
In the context of a quasi-experimental study on acquisition of cultural competence by trainee translators in the case of German-Spanish translation, a declarative knowledge questionnaire on German culture was designed and validated. This instrument, which consists of 30 items covering four cultural fields, was designed to gather data on the subjects’ declarative knowledge of German culture before performing a translation task. This paper presents the design and validation of the questionnaire, which was based on verification of content validity, criterion validity and face validity. Teachers of German as a second foreign language in the Bachelor’s degree in Translation and Interpreting at the Universitat Autònoma de Barcelona, students of German as a first and second foreign language in the same degree programme, and citizens of the Federal Republic of Germany participated in the validation of the instrument. This resulted in a validated questionnaire that may be useful for other researchers and teachers. Despite its utility, the instrument has some limitations: it does not enable replication of the study with other samples without calibrating it, it is not stable over long periods of time and it only measures cultural knowledge at a nation-state level.